Representation and Negotiation of Masculinities in South Asian English Fiction: Feminist Critical Discourse Analysis (Journal of Asian Development Studies, 2024)
This study traces the representation and negotiation of masculinities in Shamsie’s Home Fire. The analysis and discussion are based, on the one hand, on the deconstruction of Connell’s (1995) models of hegemonic masculinities in the novel and, on the other hand, on the exploration of alternative reshaping and more dialogical models of masculinities as stated in the theory of performativity by Judith Butler (1990, 1999) and represented in the selected fiction. For the data analysis, theoretical insights were taken from the feminist critical discourse analysis. The findings of the study reveal that individuals acknowledge themselves either as masculine or feminine referring to their gender identity. Sociologists intend to refer to gender as an essential status because it is widely recognized as a significant factor in determining identity, involvement in institutions, socialization, and opportunities in life. The negotiation of masculinities is suggested to make society more humane and balanced where individuals express their potential and personality according to their own choices.